Multiple Slip Effects on Unsteady MHD Casson Nanofluid Flow over a Porous Stretching Sheet - Reddy, G. Venkata Ramana; Sekhar, K.V.Chandra; Falodun, Bidemi Olumide (Journal of Applied Nonlinear Dynamics, 2026)
A speculative investigation has been presented on explore the salient features of multiple slip effects on MHD Casson nanofluid flow over a porous stretching sheet in the presence of Soret effect, thermal radiation and chemical reaction are numerically examined. We consider an applied magnetic field and stretching sheet time-dependent, which moves with non-uniform velocity. For the transformation of governing partial differential equations into a system of coupled nonlinear ordinary differential equations, suitable similarity variables are used. The transformed equations are then solved numerically by applying Runge-Kutta Fehlberg method with shooting technique. The influences of the various physical parameters on the velocity, temperature, and concentration profiles as well as on the skin friction coefficient, Nusselt and Sherwood numbers are discussed by the aid of graphs and tables. The imposed magnetic field produces a Lorentz force which drags the velocity of an electrically conducting Casson fluid. Due to the magnetic field strength (B_0), a higher value of Casson parameter decelerates the velocity field. Also, increase in thermal radiation parameter enhances the temperature distribution when the plate is hot.